Canadian Theatre Made for Black Women - Keleta-Mae, Naila (Theatre Research in Canada / Recherches théâtrales au Canada)

(untitled) (Graduate Centre for the Study of Drama, University of Toronto, 2018)
For close to two decades Trey Anthony has carved out a successful career as a published and produced playwright in Canada in a national theatre landscape where few playwrights enjoy sustained success. This is, in part, because Anthony is also an entrepreneur who identified Black women in Canada as a financially viable and lucrative target market and she has consistently self-produced content that is geared specifically to them. This article begins with the production history, critical response, and box office response to Anthony’s play How Black Mothers Say I Love You. It continues with an analysis of the play’s content and characters as representative of staging Black female life and it concludes with a contemplation of what Anthony’s successful cultivation of a Black female audience in Canada suggests about Canadian theatre.